Simple Method for Detecting Bacteroides spp. Bacteriocin Production - Riley, Thomas V. (1981)
Bacteroides isolates were grown anaerobically on a 0.22-μm membrane filter on an agar plate for 48 h. Cultures of an indicator strain were grown as a lawn on the agar after removal of the filter, and bacteriocin sensitivity was detected by zones of inhibition.